What is the survival rate in prenatally detected cantrell’s Pentalogy? - Pośpiech-Gąsior, Katarzyna; Słodki, Maciej; Respondek-Liberska, Maria (Prenatal Cardiology, 2016)
Cantrell’s pentalogy is a congenital defect characterized by uncompleted fusion of the anterior chest wall, resulting in an extrathoracic location of the heart. Ultrasound diagnosis during the first trimester of prenatal life is possible, and termination of pregnancy is usually chosen by pregnant women. We analysed 57 fetuses: 56 from literature and one additional recent case from our institute (from 2016) to evaluate what was the survival rate reported after prenatal diagnosis, including the possibility to terminate the pregnancy, intrauterine deaths and neonatal deaths. We found 10 survivors - 18% since 1984. Despite dismal prognosis of fetal ectopia cordis, there is a chance for postnatal survivorship probably due to evolving anatomical structures, not only in the first trimester of pregnancy but also during the following weeks of prenatal life.